Estratégias metacognitivas: um recurso para a aprendizagem da leitura na alfabetização - Monte, Sílvia Maria Teixeira (2021)
The research entitled Metacognitive Strategies: a resource for reading learning in literacy seeks to integrate the pedagogical practice and the construction of knowledge by the student, in the initial reading learnin process. The main objective is recognize metacognitive strategies that children use in reading learning in literacy process. As specific objectives, analyze the use of planning, control, and evaluation strategies used by children to carry out reading activities; reflect on the correlation between teaching strategies and performance for the use of regulation and self-regulation strategies; Develop teaching strategies that facilitate awareness of metacognitive strategies used by students. It is understood that reading is a social act and that interaction is a primordial factor for learning, and the research was based on socio-discursive authors, such as Smith (2003), Solé (1998) and Kato (2004), who do conceptual approaches and discursive of the learner's relationships with socially constructed knowledge. To investigate mental processing, the cognitive theory is taken as a reference, the main authors are: Flavell (1999), Pozo (2002), Portilho (2012) and Veiga Simão (2013, 2014). Approaching literacy issues are Scliar-Cabral (2003), Soares (2004, 2020) and Morais (2012). The research is carried out with students in the second year of elementary school, from a public school, in Fortaleza, and adopts as a research methodology the realization of a pilot project with reading tests and interviews with students for the observation and analysis of the use of metacognitive strategies. Regulation and self-regulation; in addition, it proposes the use of metacognitive strategies in teaching to investigate the intensity and quality of the use of these strategies by students and to verify the contributions to the teaching of reading. The sample set is composed of students from the second year of elementary school, from a public school in Fortaleza. Data analysis follows the self-regulation model proposed by Lopes da Silva and Veiga Simão (2013), consisting of four phases: anticipation, planning, monitoring/volition and reflection/reaction in a continuous learning cycle. From this model, it appears that students learning to read in the literacy period regulate their knowledge and can self-regulate through metacognitive strategies. The data collected indicate that students are able to think over on their own thinking, they formulate hypotheses about concepts, they adopt strategies to deal with knowledge; that change these strategies when they perceive the need and that they perceive themselves within the learning process, being able to improve the adopted procedures. With regard to teaching, there is the importance of closer monitoring of the teacher, seeking to understand the knowledge hypotheses elaborated by the student and the proposition of a strategic teaching, in order to contribute to the expansion of the students' cognitive and metacognitive development. The literature surveyed indicates that teaching based on metacognitive strategies can lead to a more systematic use of regulation and self-regulation strategies by the student, expanding their possibilities for reflection on knowledge, their motivation and autonomy in the learning process.